2017
DOI: 10.1159/000455872
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-125 Brachytherapy for Uveal Melanoma: A Systematic Review of Radiation Dose

Abstract: Aim: To investigate whether lower radiation doses may yield similar outcome measures to those from the COMS trial. Methods: A literature review of English language articles was performed using the PubMed database of the U.S. National Library of Medicine and the Cochrane Central Register of Controlled Trials using the following keywords: uveal melanoma, choroidal melanoma, primary uveal malignant melanoma, iodine-125 brachytherapy, local recurrence, local treatment failure, and local tumor control. The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…The mean dose applied to the top of the tumour did not have any effect on the occurrence of local relapse in our patients. Some similar observations were made by Echegaray et al in a meta-analysis of 15 reports in which they observed a tendency of local relapse to decrease by 0.14% with a dose increase by 1 Gy to the top of the tumour, yet this result was not statistically significant (p = 0.336) [22].…”
Section: Discussionsupporting
confidence: 74%
“…The mean dose applied to the top of the tumour did not have any effect on the occurrence of local relapse in our patients. Some similar observations were made by Echegaray et al in a meta-analysis of 15 reports in which they observed a tendency of local relapse to decrease by 0.14% with a dose increase by 1 Gy to the top of the tumour, yet this result was not statistically significant (p = 0.336) [22].…”
Section: Discussionsupporting
confidence: 74%
“…Thanks to the current methods of uveal melanoma treatment, the rate of positive effects of local treatment is about 76–100% 9,10 . Unfortunately, there are still no effective treatment methods which would allow to cure the disease completely or to prolong significantly the survival of the patients in whose case tumor spread occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Ranges of reported mean or median radiation dose to tumor apex were 62.5-104.0 Gy. Local recurrence rates ranged from 0 to 24% [27].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the study was to evaluate outcomes of I-125 brachytherapy treatment of patients with uveal melanoma, taking into account the relationship between results and the dose applied to the tumor apex [25,26,27].…”
Section: Purposementioning
confidence: 99%